Veraphis yoshitomii sp. n. (Coleoptera, Staphylinidae, Scydmaeninae) from Japan - Jałoszyński, Paweł (Zootaxa, 2014)
A new species of Eutheiini, Veraphis yoshitomii sp. n. is described from Shikoku, Japan. Diagnostic characters are discussed and key structures, including the aedeagus, are illustrated. The new species belongs to the Veraphis japonicus species group, which includes five species distributed in mountains of Japan and five possibly closely related ones in the sub-Himalayan China. The distribution of Japanese Veraphis is summarized and discussed.